3(11r-13)=

Simple and best practice solution for 3(11r-13)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(11r-13)= equation:


Simplifying
3(11r + -13) = 0

Reorder the terms:
3(-13 + 11r) = 0
(-13 * 3 + 11r * 3) = 0
(-39 + 33r) = 0

Solving
-39 + 33r = 0

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '39' to each side of the equation.
-39 + 39 + 33r = 0 + 39

Combine like terms: -39 + 39 = 0
0 + 33r = 0 + 39
33r = 0 + 39

Combine like terms: 0 + 39 = 39
33r = 39

Divide each side by '33'.
r = 1.181818182

Simplifying
r = 1.181818182

See similar equations:

| -3(12+2)=-72 | | 8+1w=3+2w | | 14-(6-3c)=4c*c | | 7-5x=-27 | | -2x+6=21 | | 0.2(15-3t)-1.8= | | 2[(6*6-5*5)+4]= | | 4n+5+8n-5=180 | | x-5.4=7.8 | | 1/32,1/16,1/8,1/4 | | 2(36-7)+3(27-3)= | | 4n+5+8n-5= | | 100x^2-264x+92=0 | | 4n+5+8n-5=90 | | (3/5n)+(9/10)=(-1/5n)-(23/10) | | 12x+8=104 | | 1.4(m+1.1)=8.4 | | [x+1]=-2 | | (36*3)-6+(7*3)(2*3)= | | 8-g-2+5g= | | 853=-18(m+862)+457 | | 50+30(10)=250+10(10) | | 2(h+24)=-2h | | -45.00+15.00=0.0O | | -5/9+20 | | 8(s+861)+-329=-641 | | 25(6)-6(6)= | | 50+30x=250+10x | | [x+20]+60+3x=180 | | 4w+5-3=-7 | | 4(x-5)-8/(-3)=12 | | 241-f=50 |

Equations solver categories